Characteristic Of Silica Sand From Kuantan, Pahang - Azizan, Muhammad Ikhram Hakim (Universiti Sains Malaysia, 2022)
The purpose of this research is to characterize silica sand sample and to recover thevaluable minerals found in silica samples obtained from YP Mining Sdn. Bhd. The sample are taken at two different spot at different depth which are 1 to 4 meter depth. There are four method of characterization were implemented in this research such as Particle Size Distribution, X-ray Fluorescence (XRF), Micro X-ray Fluorescence, Microscopic Study(SEM/EDX). From this study, silica (SiO2), R]rutile (TiO2), corundum(Al2O3), and hematite (Fe2O3) were found in silica sand in Kuantan, Pahang. The size of the sample that was chosen for this research is the ranges from 2.8 mm to less than 0.053 mm. As the result, from composition analysis, the composition of Silica at spot A is higher compare to spot B. Therefore, grade at spot A is higher compare to spot B. At spot A contain less of corundum and rutile. However, the grade does not effect the research because the main objective of this research was know the size distribution of silica sand at different level and analyze the mineralogy of the bulk samples taken from YP Mining Sdn Bhd, Pahang.